Harnessing Switchgrass for Sustainable Energy: Bioethanol Production Processes and Pretreatment Technologies - Ünyay, Hilal; Perendeci, Nuriye, Altınay; Piersa, Piotr; Szufa, Szymon; Skwarczynska-Wojsa, Agata (MDPI Open Access Journals, 2024)
This paper investigates bioethanol production from switchgrass, focusing on enhancement of efficiency through various pretreatment methods and comparing two bioethanol production processes: simultaneous saccharification and fermentation (SSF) and separate hydrolysis and fermentation (SHF). Physical, chemical, and biological pretreatment processes are applied to enhance the breakdown of switchgrass’s lignocellulosic structure. Effects of pretreatments, enzymatic hydrolysis, and fermentation on ethanol yield are discussed in detail. The comparative analysis reveals that SSF yields higher ethanol outputs within shorter times by integrating hydrolysis and fermentation into a single process. In contrast, SHF offers more control by separating these stages. The comparative analysis highlights that SSF achieves higher ethanol yields more efficiently, although it might restrict SHF’s operational flexibility. This study aims to provide a comprehensive overview of the current pretreatments, hydrolysis methods, and fermentation processes in bioethanol production from switchgrass, offering insights into their scalability, economic viability, and potential environmental benefits. The findings are expected to contribute to the ongoing discussions and developments in renewable bioenergy solutions, supporting advancing more sustainable and efficient bioethanol production techniques.
This article belongs to the Section A4: Bio-Energy
Keywords: bioethanol; hydrolysis; pretreatment; separate hydrolysis and fermentation; simultaneous saccharification and fermentation; switchgrass